Alterted Adipogenesis of Human Mesenchymal Stem Cells by Photobiomodulation Using 1064 nm Laser Light. Issue 2 (3rd June 2020) - McColloch, Andrew; Liebman, Caleb; Liu, Hanli; Cho, Michael
Abstract : Background and Objectives: Photobiomodulation (PBM) describes the influence of light irradiation on biological tissues. Laser light in the near‐infrared (NIR) spectrum has been shown to mitigate pain, reduce inflammation, and promote wound healing. The cellular mechanism that mediates PBM's effects is generally accepted to be at the site of the mitochondria, leading to an increased flux through the electron transport chain and adenosine triphosphate (ATP) production. Moreover, PBM has been demonstrated to reduce oxidative stress through an increased production of reactive oxygen species (ROS)‐sequestering enzymes. The aim of the study is to determine whether these PBM‐induced effects expedite or interfere with the intended stem cell differentiation to the adipogenic lineage. Study Design/Materials and Methods: To determine the effects of 1064 nm laser irradiation (fluence of 8.8–26.4 J/cm 2 ) on human mesenchymal stem cells (hMSCs) undergoing adipogenic differentiation, the ATP and ROS levels, and adipogenic markers were quantitatively measured. Results: At a low fluence (8.8 J/cm 2 ) the ATP increase was essentially negligible, whereas a higher fluence induced a significant increase. In the laser‐stimulated cells, PBM over time decreased the ROS level compared with the non‐treated control group and significantly reduced the extent of adipogenesis. A reduction in the ROS level was correlated with a diminished lipid accumulation, reduced production of adipose‐specific genetic markers, and delayed the chemically intended adipogenesis. Conclusion: We characterized the use of NIR light exposure to modulate adipogenesis. Both the ATP and ROS levels in hMSCs responded to different energy densities. The current study is expected to contribute significantly to the growing field of PBM as well as stem cell tissue engineering by demonstrating the wavelength‐dependent responses of hMSC differentiation. Lasers Surg. Med. © 2020 Wiley Periodicals LLC.